PENGARUH VARIASI LATIHAN PASSING BAWAH DENGAN MODEL HURUF TERHADAP HASIL PASSING BAWAH BOLA VOLI PUTRI KLUB TVRI MEDAN TAHUN 2021 - Rezma Annisa Fitri; Yan Indra Siregar (Journal Physical Health Recreation (JPHR), 2021)
This study aims to determine whether the variation of under passing with the letter model can improve the results of under-passing in the Medan TVRI club volleyball athletes in 2020, the exercise of the under-passing variation with the letter model is an exercise that can help improve the under-passing technique in the game.. test after the end of the workout in the last week. Hypothesis analysis, namely, the effect of the variation of the under-passing training with the letter model on the under-passing of volleyball athletes of the Medan TVri club female athletes in 2021, obtained a Thitung hypothesis test of 3,35 Furthermore, compared with the t table with dk = n-1 = 10-1 = 9 at the significant level α = 0.05 = 2.26. In the hypothesis testing criteria it is stated that at tcount> ttable (3,25> 2.26) with α = 0.05 then Ho is rejected and Ha is accepted. So it can be concluded that there is a significant effect of under-wall passing practice on under-passing with variations of volleyball letters in women's volleyball athletes at the Medan TVRI club in 2021.